Cellular evaluation of the metal-organic framework PCN-224 associated with inflammation and autophagy. (February 2021) - Li, Xiuping; Qin, Hua; Zhou, Zehao; Li, Yang; Wang, Ji; Lin, Mo; Dong, Xuemeng; Yang, Man; Li, Lele
Abstract: Metal-organic frameworks (MOFs) are innovative porous structures consisting of metal ions and organic ligands, which have been verified for extraordinary applications in nanomedicine and pharmaceuticals. PCN-224 is a type of Zr-based MOFs, which has recently emerged as one of the most attractive nanomaterials for various applications, such as drug delivery, bioimaging and cancer therapy due to its favorable and fascinating physical-chemical properties. However, the safety evaluation and the potential toxicological properties remain unclear. In this study, the general cytotoxicity of PCN-224 were examined in both human hepatocytes L-02 cells and mouse macrophages RAW264.7. Furthermore, the effect of inflammation and autophagy were measured in L-02 cells. The results indicated that PCN-224 was engulfed in L-02 cells and subsequently resulted in morphological changes, cell membrane destruction, and oxidative stress in L-02 cells. PCN-224 might trigger inflammation by promoting the secretion of inflammatory factors such as Tumor necrosis factors (TNF-α) and Interleukin (IL-6). PCN-224 might induce autophagosome accumulation and subsequently autophagic dysfunction. Additionally, PCN-224 induced cytotoxicity in RAW264.7 cells and increased the protein levels of the inflammasome component NLR Family Pyrin Domain Containing 3 (NLRP3) molecular, which indicated its cellular effects in different cell types. All of these results will support the reasonable use of PCN-224. Highlights: The cellular effect of the metal organic framework was evaluated. Evaluation of PCN-224-induced oxidative stress, inflammation and autophagy. Toxicological data of metal organic framework materials have been expanded.